2005
DOI: 10.1073/pnas.0408972102
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing inducible nitric-oxide synthase in living cells with a heme-binding fluorescent inhibitor

Abstract: The study of nitric-oxide synthase (NOS) physiology is constrained by the lack of suitable probes to detect NOS in living cells or animals. Here, we characterized a fluorescent inducible NOS (iNOS) inhibitor called PIF (pyrimidine imidazole FITC) and examined its utility for microscopic imaging of iNOS in living cells. PIF binding to iNOS displayed high affinity, isoform selectivity, and heme specificity, and was essentially irreversible. PIF was used to successfully image iNOS expressed in RAW264.7 cells, HEK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…Cell lysates were processed as described elsewhere (16,25). All of the experiments were repeated at least three times and the average of all is shown in the results.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell lysates were processed as described elsewhere (16,25). All of the experiments were repeated at least three times and the average of all is shown in the results.…”
Section: Methodsmentioning
confidence: 99%
“…RAW264.7 and HEK293 (ATCC) cells were cultured as described elsewhere (25). Cells were pretreated with 2,4-dioxoheptanoic acid (250 μM) for 2-3 d to make heme deficient.…”
Section: Methodsmentioning
confidence: 99%
“…2B). Thus, acquisition of heme by Duox is essential for association with DuoxA, a scenario reminiscent of Nox2-p22 phox heterodimer or iNOS homodimer formation (DeLeo et al, 2000;Panda et al, 2005;Yu et al, 1997). In accord, heme incorporation was essential for H 2 O 2 generation by Duox enzymes (Fig.…”
Section: Heterodimerization Of Duox-duoxa Is Heme Dependentmentioning
confidence: 99%
“…Deletion of analogous residues from the N-terminal regions in nNOS and eNOS did not completely abrogate their capability for dimer formation (44,45). Such differences may explain the different affinities and dimerization inhibitory potential of pyrimidine imidazoles for the three NOS isoforms (27,30). In fact, the inhibitory potency of bulky pyrimidine imidazoles was found to be in the order of eNOS/nNOS/iNOS as 1:200:1000 (27).…”
mentioning
confidence: 99%
“…Original studies by our group on the effect of N 1 -substituted pyrimidine imidazoles, like clotrimidazole on iNOS-synthesizing RAW cells, revealed that they inhibited iNOS activity by preventing heme insertion (26). Later studies with PID-like compounds showed that they bind to the NOS heme during its expression and produce an irreversible iNOSmonomer-inhibitor complex (28,30). Indeed, among the imidazoles examined for iNOS dimerization inhibition, pyrimidine imidazoles have shown considerable promise to qualify as effective nontoxic iNOS inhibitors (27,28).…”
mentioning
confidence: 99%